2020
DOI: 10.6018/educatio.432971
|View full text |Cite
|
Sign up to set email alerts
|

Estudio piloto de variables socio-emocionales, ansiedad y flow en alumnos de grado profesional de música mediante actividades BAPNE

Abstract: El objetivo de esta investigación es hacer un análisis exploratorio a través de un diseño cuasi-experimental con grupo control no equivalente de los efectos que las actividades del método BAPNE tienen sobre las emociones, la ansiedad, el “flow” y la conducta social en alumnos de Grado Profesional de Música. Los resultados obtenidos apoyan nuestras hipótesis de investigación con diferencias estadísticamente significativas en medidas pre-post del grupo experimental con p< .05 para emocio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
2
1
1
Order By: Relevance
“…In variable O our results disagree with those provided by Romero-Naranjo (2020) andRos et al (2019) since in both cases they find significant differences in favor of the experimental group. In our case, neither of the two groups significantly decreases the number of omissions, although when comparing them a significant difference appears in which the control group makes fewer omissions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In variable O our results disagree with those provided by Romero-Naranjo (2020) andRos et al (2019) since in both cases they find significant differences in favor of the experimental group. In our case, neither of the two groups significantly decreases the number of omissions, although when comparing them a significant difference appears in which the control group makes fewer omissions.…”
Section: Discussioncontrasting
confidence: 99%
“…It is important to highlight that all the research has a quantitative approach, quasi-experimental design, control and experimental group, repeated measures through validated tests, non-probabilistic sampling by convenience, a sample of between 40 and 105 participants and an intervention that ranges from three to six months with a minimum of two 50-minute sessions per week. Most studies have been conducted with students in Primary Education (Arnau-Mollá & Romero-Naranjo, 2020;Carretero-Martínez et al, 2014;Castelló-Juan et al, 2019;Cozzutti et al, 2017;Torró-Biosca et al, 2019), andSecondary (Álvarez-Morales &Romero-Naranjo, 2019;Fabra-Brell & Romero-Naranjo, 2017;Latre-Navas et al, 2019;Piqueres-Juan et al, 2019;Romero-Naranjo & Sayago et al, 2023), although also in Conservatories (Moral et al, 2020;Ros-silla et al, 2019) and in elderly people (González et al, 2019) among others. All the studies have revealed statistically significant results, but even so, we consider that we need larger studies with a greater number of subjects to be able to assert that the BAPNE method contributes to an improvement in selective attention.…”
Section: Introductionmentioning
confidence: 99%
“…Body percussion in physical activity and sport sciences has an exclusive program that differentiates it from activities in other subjects (Romero-Naranjo, 2013a, 2013b, 2013c, 2017, 2018, 2019, such as visual arts (Alonso-Sanz & Romero-Naranjo, 2013), music (Romero-Naranjo, 2019, theater , learning a foreign language (Fernández-Molina et al, 2019), ethnography (Di Russo & Romero-Naranjo, 2021a, 20221b;Romero-Naranjo, 2008), socioemotional (Fabra-Brell & Romero-Naranjo, 2017;Moral-Bofill et al, 2020), etc. In the sciences of physical activity, the Bapne method provides a whole protocol of practical activities divided into two main lines.…”
Section: Introductionmentioning
confidence: 99%
“…"Body percussion" en las ciencias de la actividad física y el deporte es una materia interdisciplinar, que puede ser aplicada dentro del ámbito de la expresión corporal con el objetivo de trabajar nuestro esquema corporal, y posiblemente mejorar, la condición física. "Body percussion" o percusión corporal, aporta interesantes recursos e investigaciones avaladas por publicaciones de alto impacto (Arnau-Mollá & Romero-Naranjo, 2022a, 2022bSerna-Domínguez et al, 2018), que evidencian posibles mejoras de la red atencional del alumnado de Educación Primaria (Arnau-Mollá & Romero-Naranjo, 2020); Carretero-Martínez et al, 2014;Castelló-Juan et al, 2019;Torró-Biosca et al, 2019), y Secundaria (Álvarez-Morales & Romero-Naranjo, 2019;Fabra-Brell & Romero-Naranjo, 2017;Latre-Navas et al, 2019;Piqueres-Juan et al, 2019;Romero-Naranjo & Sayago et al, 2022), aunque también en alumnado de Conservatorios de música (Moral-Bofill et al, 2020;Ros-Silla et al, 2019) y en personas mayores (González et al, 2019), entre otros. Existen publicaciones que aportan recursos con las artes visuales (Alonso-Sanz & Romero-Naranjo, 2015), en el aprendizaje de una lengua extranjera (Fernández et al, 2021), el conocimiento de danzas con percusión corporal en otras culturas (Di Russo & Romero-Naranjo, 2021aRomero-Naranjo, 2008;2013b, 2016 así como aportar recursos prácticos basados en la etnomusicología (González-Sánchez et al, 2021;Romero-Naranjo, 2012;2013a;2020c, 2020e, 2022a, 2022bRomero-Naranjo & González, 2022a, 2022bRomero-Naranjo & Sayago-Martínez, 2021a…”
Section: Introductionunclassified